2015
DOI: 10.1186/s13578-015-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Transient blocking of NK cell function with small molecule inhibitors for helper dependant adenoviral vector-mediated gene delivery

Abstract: One major challenge in gene therapy is the host immune responses against viral vectors. Previous studies indicate the involvement of NK cells in stunted gene expression in viral vector mediated gene therapy. To understand the problem of the immune responses, we have developed an in-vitro co-culture system with human NK cell line, macrophages and airway epithelial cells. We showed that small molecule blockers, CAPE and ruxolitinib, for NF-κB and JAK-STAT pathways, respectively, significantly inhibited cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Lastly, Ankathatti and Hu (58) showed, in a study with human cell lines, that small molecule blockers, including ruxolitinib, for JAK-STAT pathway, significantly inhibited cytokine secretion by macrophages activated by viral infectious trigger. Usually, macrophages respond to viral infection by releasing soluble mediators, helping in the recruitment of innate, and adaptative effector cells.…”
Section: Cellular Targets Of the Immunosuppressive Activity Of Ruxolimentioning
confidence: 99%
“…Lastly, Ankathatti and Hu (58) showed, in a study with human cell lines, that small molecule blockers, including ruxolitinib, for JAK-STAT pathway, significantly inhibited cytokine secretion by macrophages activated by viral infectious trigger. Usually, macrophages respond to viral infection by releasing soluble mediators, helping in the recruitment of innate, and adaptative effector cells.…”
Section: Cellular Targets Of the Immunosuppressive Activity Of Ruxolimentioning
confidence: 99%
“…Later studies confirmed that IL-12 was completely blocked by ruxolitinib, as well as IL-15 and the phosphorylation of STAT5, resulting in a functional impairment of IFN-γ production by NK cells (Figure 3, ruxolitinib) [131]. An inhibition of cytokine secretion by macrophages was also reported, possibly effecting NK cell recruitment, maturation, and killing activity [132]. The reported impairment of DC function also resulted in the impaired induction of antigen specific T cell responses [130].…”
Section: Jak Inhibitorsmentioning
confidence: 82%
“…However, some specific concerns should be taken into account: as other JAK inhibitors, ruxolitinib impairs the capability of antigen presenting cells (such as macrophages and dendritic cells) to produce, among others, type I interferons, Il-12, IL-15, and IL-23. This event negatively influences NK activation, antigen presentation and Th1/Th17 polarization, with consequent alterations in antigen-specific T cells response, including viral clearance, providing a possible mechanistic explanation for the increase of infection rates in patients with MPN undergoing longterm ruxolitinib treatment (36,(79)(80)(81)(82)(83)(84)(85)(86)(87).…”
Section: Targeting the Jak Signaling: The Promise Of Ruxolitinibmentioning
confidence: 99%